The Antiviral Effects of the Symbiont Bacteria Wolbachia in Insects - Pimentel, André C.; Cesar, Cássia S.; Martins, Marcos; Cogni, Rodrigo (Frontiers in Immunology, 2021)
Wolbachia is a maternally transmitted bacterium that lives inside arthropod cells. Historically, it was viewed primarily as a parasite that manipulates host reproduction, but more recently it was discovered that Wolbachia can also protect Drosophila species against infection by RNA viruses. Combined with Wolbachia’s ability to invade insect populations due to reproductive manipulations, this provides a way to modify mosquito populations to prevent them transmitting viruses like dengue. In this review, we discuss the main advances in the field since Wolbachia’s antiviral effect was discovered 12 years ago, identifying current research gaps and potential future developments. We discuss that the antiviral effect works against a broad range of RNA viruses and depends on the Wolbachia lineage. We describe what is known about the mechanisms behind viral protection, and that recent studies suggest two possible mechanisms: activation of host immunity or competition with virus for cellular resources. We also discuss how association with Wolbachia may influence the evolution of virus defense on the insect host genome. Finally, we investigate whether the antiviral effect occurs in wild insect populations and its ecological relevance as a major antiviral component in insects.